Contribution à l’étude génétique du polymorphisme R381Q du gène IL23R dans la survenue de la Leucémie Myéloïde Aiguë dans un échantillon de l’Ouest Algérien - BOUBEGRA, Fatima; BENDIDA, Amina (My University, 2025)
Acute myeloid leukemia (AML) is a malignant hematologic disorder characterized by the rapid proliferation of immature myeloid cells, severely affecting the bone marrow and peripheral blood. Despite therapeutic advances, the genetic factors underlying its pathogenesis remain only partially understood. In this context, the present study focused on the rs11209026 (R381Q) polymorphism located in the IL23R gene, which is known for its involvement in chronic inflammatory diseases and certain types of cancer. The primary objective of this work was to assess the potential association between this polymorphism and the risk of developing AML within a sample population from Western Algeria. To achieve this, a total of 48 DNA samples (24 patients diagnosed with AML and 24 healthy controls) were analyzed using TaqMan real-time PCR, allowing for accurate and specific detection of allelic variations. The resulting data were statistically analyzed to determine the genotypic and allelic distribution between the two groups. The results revealed no significant association between the rs11209026 polymorphism and AML in our sample. This lack of correlation suggests that this single nucleotide polymorphism (SNP) alone does not constitute a major risk factor for AML in the studied population. In conclusion, although no genetic association was found between the R381Q SNP and AML, our findings contribute to a better understanding of the genetic landscape of AML and highlight the importance of further investigations into other genetic variants and in larger cohorts to better elucidate the molecular mechanisms involved in this disease.
Keywords: AML, IL23R, rs11209026 polymorphism, TaqMan PCR, genetics, Western Algeria